Some Studies on D-Gun Sprayed ASTM SAE213 T22 Steel for High Temperature Applications - A.S Walia; S. S Aulakh; G. Kaushal (Asian Review of Mechanical Engineering, 2013)
Detonation gun spray coatings are known for their high density, high bond strength and better wear/corrosion resistance. In this study, detonation gun spray technique was used to deposit WC-12Co and Cr3C2-25NiCr coating on boiler steel ASTM SAE213 T22 steel. The specimens with and without coating were subjected to cyclic oxidation at 500oC for 50 cycles in air environment to ascertain usefulness of the coating at the said temperature. The weight change technique was used to establish the kinetics of oxidation/corrosion. X-ray diffraction (XRD) and FE-SEM/EDS techniques were used to analyze the exposed samples. The behavior of the uncoated and coated samples supported by various characterization techniques in detail have been reported in the present study.